Effect of deposit chemistry on microbial community structure and activity: Implications for under-deposit microbial corrosion - Maria A. Diaz-Mateus (14590028) (2023)
Introduction The deposition of solid particles carried by production fluids from oil and gas companies in horizontal surfaces of different assets has shown to cause severe localised corrosion. Sand, one of the most common deposits in the energy sector pipelines, is frequently mixed with crude, oil, asphaltenes, corrosion inhibitors, and other organic compounds. For this reason, they might favour the metabolic activity of native microbial communities. This study aimed to determine the impact of sand-deposit chemical composition on the microbial community structure and functional attributes of a multispecies consortium recovered from an oilfield and the resulting risk of under-deposit microbial corrosion of carbon steel. Methods Sand deposits recovered from an oil pipeline were used in their raw form and compared against the same deposits exposed to heat treatment to remove organic compounds. A four-week immersion test in a bioreactor filled with synthetic produced water and a two-centimeter layer of sand was set up to assess corrosion and microbial community changes. Results The raw untreated deposit from the field containing hydrocarbons and treatment chemicals resulted in a more diverse microbial community than its treated counterpart. Moreover, biofilms developed in the raw sand deposit exhibited higher metabolic rates, with functional profile analysis indicating a predominance of genes associated with xenobiotics degradation. Uniform and localized corrosion were more severe in the raw sand deposit compared to the treated sand. Discussion The complex chemical composition of the untreated sand might have represented an additional source of energy and nutrients to the microbial consortium, favoring the development of different microbial genera and species. The higher corrosion rate obtained under the untreated sand suggests that MIC occurred due to syntrophic relationships between sulphate reducers or thiosulphate reducers and fermenters identified in the consortium. Other Information Published in: Frontiers in Microbiology License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3389/fmicb.2023.1089649